High specificity of metagenomic next-generation sequencing using protected bronchial brushing sample in diagnosing pneumonia in children - Zhang, Chunyan; Li, Zheng; Wang, Mengyuan; Zhou, Jiemin; Yu, Wenwen; Liu, Huifang; Hu, Bingxue; Wang, Shifu (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Lower respiratory tract infections are the leading causes of morbidity and mortality in children worldwide. Timely and accurate pathogen detection is crucial for proper clinical diagnosis and therapeutic strategies. Low detection efficiency of conventional methods and low specificity using respiratory samples seriously hindered accurate detection of pathogens.In this study, we retrospectively enrolled 1032 children to evaluate the performance of metagenomics next-generation sequencing (mNGS) using bronchoalveolar lavage fluid sample (BALF) and protected bronchial brush sample (BB) in diagnosing pneumonia of children. In addition, conventional tests (CT) were also performed.The specificity of BB mNGS (67.3% (95% CI 58.6-75.9%)) was significantly higher than that of BALF mNGS (38.5% (95% CI 12.0-64.9%)). The total coincidence rate of BB mNGS (77.6% (95% CI 74.8-80.5%)) was slightly higher than those of BALF mNGS (76.5% (95% CI 68.8-84.1%)) and CT (38.5% (95% CI 35.2-41.9%)). During the epidemics of Mycoplasma pneumoniae, the detection rate of M. pneumoniae in >6y group (81.8%) was higher than that in 3-6y (78.9%) and < 3y groups (21.5%). The highest detection rates of bacteria, fungi, and viruses were found in <3y, >6y, and 3-6y groups, respectively. mNGS detection should be performed at the duration of 5-7 d after the start of continuous anti-microbial therapy or at the duration of 6-9 d from onset to mNGS test.Conclusions: This is the first report on evaluating the performance of BB mNGS in diagnosing pulmonary infections of children on a large scale. Based on our findings, extensive application of BB mNGS could be expected.